Long-term clinical outcomes of Zikaassociated Guillain-Barré syndrome (2018)
Zika virus infection has been associated with the development of a spectrum of neurologic disease including Guillain–Barré syndrome (GBS)1. GBS is an autoimmune disorder of the peripheral nervous system often triggered by a preceding infection. The mechanism of Zika-associated GBS (Z-GBS) and the long-term clinical course is unknown. The purpose of this study was to describe the 2-year clinical course of Z-GBS in order to provide further insights into disease pathogenesis and prognosis.